TINJAUAN YURIDIS TERHADAP BATAS KEPEMILIKAN MODAL ASING PADA INDUSTRI PERBANKAN INDONESIA DALAM KERANGKA WORLD TRADE ORGANIZATION - Aditya Fahrizi Mushollin; Sudiyana (Fakultas Hukum Universitas Janabadra, 2025)
This research aims to find out and analyze the regulation of foreign capital ownership in the Indonesian banking sector, which can reach 99%, whether it can provide welfare for the Indonesian people, especially for people of working age. This thesis writing uses a type of normative legal research. This research uses a statutory approach (statute approach) and a historical approach (historical approach) which aims to sharpen the analysis of research legal materials in order to find out the rationale for the legal regulations governing foreign capital ownership in the Indonesian banking sector which can reaching 99% can provide welfare for the Indonesian people, especially people of working age. The results of the research are that banks in Indonesia implemented foreign capital liberalization as a result of the crisis that hit Indonesia in the past. The World Trade Organization (WTO) is currently the only international organization that specifically deals with trade issues between countries in the world. This organization was officially founded on January 1, 1995, as a result of the Uruguay Round (1986-1994) which agreed on the Agreement Establishing the World Trade Organization. The World Trade Organization (WTO) was formed as a successor and complement to the General Agreement on Tariffs and Trade (GATT) 1947. The World Trade Organization (WTO) as an international trade organization is expected to bridge the interests of all countries in the world in the trade sector through the provisions that have been established. jointly agreed by member countries. The opportunity for foreigners to own up to 99% of bank shares has positive implications, but there are also concerns that it could have negative implications. This positive implication is the creation of Good Corporate Governance (GCG) and increased bank performance, especially due to strengthening the capital structure.